Izziv: debatni klub za participacijo v današnji civilizaciji - Bajda, Urška (Šolska knjižnica, 2016)
While realising that it is getting harder to find our bearings in the chaos of online information, we are simultaneously acknowledging that of all the types of literacy, information literacy is becoming the principal one for a functional individual. The paper presents the debate as a method of critical thinking, describes the course of Slovenian primary school debate tournaments, and adds a few guidelines for the critical evaluation of information sources, which are accessible on the World Wide Web through information and communication technology. It also presents the implementation of the extra-curricular activity of debate clubs. The author bases her argument on the advantages of carrying out a debate in the school library as the place in which information sources are located and critically evaluated.
Keywords: debatni klub; informacijska pismenost; kritično mišljenje; kritično vrednotenje; osnovne šole; svetovni splet; šolske knjižnice; učne metode